State and religion in Israel : a philosophical-legal inquiry - Sapir, Gideon; Statman, Daniel (Cambridge : Cambridge University Press, 2019)
State and Religion in Israel begins with a philosophical analysis of the two main questions regarding the role of religion in liberal states: should such states institute a'Wall of Separation' between state and religion? Should they offer religious practices and religious communities special protection? Gideon Sapir and Daniel Statman argue that liberalism in not committed to Separation, but is committed to granting religion a unique protection, albeit a narrower one than often assumed. They then use Israel as a case study for their conclusions. Although Israel is defined as a Jewish state, its Jewish identity need not be interpreted religiously, requiring that it subjects itself to the dictates of Jewish law (Halakha). The authors test this view by critically examining important topics relevant to state and religion in Israel: marriage and divorce, the drafting of yeshiva students into the army, the character of the Sabbath and more.
Part 1: Theory -- 1. Liberalism and neutrality (1): Arguments against support -- 2. Liberalism and neutrality (2): Arguments against preference -- 3. The assumed dangers of religion -- 4. Religious reasons for separation -- 5. Freedom of religion -- 6. Protection of religious feelings -- 7. Freedom from religion -- 8. Religious coercion: the place of religious arguments in the public sphere -- Part 2: From theory to practice -- 9. Marriage and divorce -- 10. Religious education -- 11. Serving religious needs -- 12. Drafting yeshiva students into the army -- 13. The Sabbath in a Jewish State -- 14. The supreme court on the protection of and from religion -- 15. Minority religions in Israel.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: Judaism and state -- Israel -- Philosophy; Religion and state -- Israel -- Philosophy; Democracy -- Religious aspects -- Judaism; Israel -- Politics and government; Jewish philosophy -- Israel -- History -- 21st century